Methodological approaches to epidemiological surveillance of chronic non-infectious diseases - О.V. Berdnyk; М.Yu. Аntomonov; N.S. Polka; О.P. Rudnytska (Medičnì Perspektivi, 2022)
In the context of the constant growth of the burden of chronic non-infectious diseases, surveillance needs in supplementing traditional statistical health indicators with criteria characterizing the processes of chronicity of pathology. Aim: to scientifically substantiate and develop statistical characteristics of chronic non-infectious diseases suitable for surveillance in the public health system. Methods used: bibliographic; statistical (for analyzing materials about the health of the population); mathematical (for constructing formulas and indices); calculational (to calculate indicators of pathology chronicity); epidemiological (to assess the chronicity of diseases of different classes). The initial statistical information was the materials of the Ministry of Health of Ukraine on mortality, general and primary morbidity of the population for six classes of diseases, which include the most common chronic diseases. The proposed set of indicators, which includes both the indices available in the scientific literature and those developed by us, contains the following characteristics: statistical indicators of official reporting, indicators of pathology chronicity, mortality and survival of the population, and the hazard index of chronic diseases, which can be considered an integrated indicator characterizing chronic diseases. Diversified characteristics of chronic non-infectious diseases of different classes of diseases were established, which is reflected, in particular, on the relationship between chronic diseases with preserved and lost viability. For diseases of the musculoskeletal system, one fatal case accounts for more than 9000 cases of chronic diseases with preserved viability; for diseases of the circulatory system, this indicator reaches only 58, and for neoplasms – only 22. This corresponds with the assessment of the hazard index: chronic diseases (respectively, 0.7; 153.7; 328.5 cu). The use of the proposed set of indicators makes it possible to carry out a comparative analysis of the danger of chronicity of diseases of certain classes, to track the change in these processes over time, being an important part of managing the frequency and outcomes of chronic diseases.